Simplified pairwise ranking for prioritisation of agricultural development intervention in Masisi, Democratic Republic of Congo. Issue 1 (2nd January 2023) - De Marinis, Pietro; Sali, Guido
ABSTRACT: Development Cooperation initiatives face complex real-world decision-making problems. The present action research investigates the use of Simplified Pairwise Ranking in a case study related to the identification of priority agricultural development interventions in the Collectivity of Katoyi, Nord Kivu, Democratic Republic of Congo. The study identifies roads building, technical training and follow-up, and improved varieties' introduction as the first three priority interventions. The dissertation about the applied methodology against the existing criticism provides information on how simplified pairwise ranking can be a useful and scientifically sound technique for eliciting discussion among a multidisciplinary group and for prioritising alternatives in agricultural development.